Membrane Reactors - Drioli, Enrico; Fontananova, Enrica (Advanced Membrane Technology and Applications, 2008)
This chapter contains sections titled: State‐of‐the‐Art On Catalytic Membrane Reactors Advanced Oxidation Processes for Wastewater Treatments Selective Oxidations Biocatalytic Membrane Reactors Catalytic Crystals Inorganic Membrane Reactors Microreactors Conclusions Acknowledgments References